Virtual Reality Training for Public Speaking—A QUEST-VR Framework Validation - Poeschl, Sandra (Frontiers in ICT, 2017)
Good public speaking skills are essential in many professions as well as everyday life, but speech anxiety is a common problem. While it is established that public speaking training in Virtual Reality is effective, comprehensive studies on the underlying factors that contribute to this success are rare. The QUEST-VR framework for evaluation of VR applications is presented that includes system features, user factors, and moderating variables. Based on this framework, variables that are postulated to influence the quality of a public speaking training application were selected for a first validation study. In a cross-sectional, repeated measures laboratory study (N = 36 undergraduate students; 36% men, 64% women, mean age = 26.42 years (SD = 3.42)), the effects of task difficulty (independent variable), ability to concentrate, fear of public speaking, and social presence (covariates) on public speaking performance (dependent variable) in a virtual training scenario were analyzed, using stereoscopic visualization on a screen. The results indicate that the covariates moderate the effect of task difficulty on speech performance, turning it into a non-significant effect. Further interrelations are explored. The presenter’s reaction to the virtual agents in the audience shows a tendency of overlap of explained variance with task difficulty. This underlines the need for more studies dedicated to the interaction of contributing factors for determining the quality of VR public speaking applications.